2014
DOI: 10.14430/arctic4357
|View full text |Cite
|
Sign up to set email alerts
|

Equipped for Life in the Boreal Forest: The Role of the Stress Axis in Mammals

Abstract: ABSTRACT. The hypothalamic-pituitary-adrenal axis (stress axis) plays a central role in equipping mammals to succeed in the challenging environment of the boreal forest. Over the last 20 years, we have tackled a broad range of topics to understand how the stress axis functions in four key herbivore species. The central challenge for snowshoe hares is coping with their predators, whereas for the others, it is primarily coping with each other (especially during reproduction) and with their physical environment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 85 publications
(113 reference statements)
0
24
0
Order By: Relevance
“…Because the project was designed for the long term, we could not use destructive sampling procedures, so percent cover was used as a measure of abundance. The major plant study began in 1990 and continues to date; in 20 years, the study has spanned two complete snowshoe hare cycles and three peaks in hare population density (Boonstra et al, 2014).…”
Section: Study Area and Experimental Designmentioning
confidence: 99%
“…Because the project was designed for the long term, we could not use destructive sampling procedures, so percent cover was used as a measure of abundance. The major plant study began in 1990 and continues to date; in 20 years, the study has spanned two complete snowshoe hare cycles and three peaks in hare population density (Boonstra et al, 2014).…”
Section: Study Area and Experimental Designmentioning
confidence: 99%
“…Accordingly, habitat-specific variations in predation pressure may be a possible cause for the detected differences in the physiologic stress response as well as for the differences in population densities. Studies on other small mammals indicate that HPA-axis functioning is altered in varying degrees by reproductive effort and food scarcity, which may have major influences on fitness (Boonstra et al, 2014). Thus by assessing potential stressors and their impact on the life history of the edible dormouse habitat-specific differences in survival and reproduction might be further unraveled.…”
Section: P/l Ratio Does Not Correlate With High Population Densitiesmentioning
confidence: 99%
“…, Boonstra et al. ). A number of laboratory and field studies have shown that predators or predator cues can change prey stress physiology and have negative effects on reproduction (Hayward and Wingfield , Eriksen et al.…”
Section: Introductionmentioning
confidence: 98%
“…, , Boonstra et al. ). The apparent stress reaction induced by predators is the activation of the hypothalamic–pituitary–adrenal (HPA) axis that causes adrenal glands to secrete epinephrine and glucocorticoids (Sapolsky et al.…”
Section: Introductionmentioning
confidence: 99%